PKM Mural in Maumere 2 Catholic Elementary School Building - Yesita Madona Vikmart Mada Hekopung; Maria Rut Xaveriana da Silva; Maria Imakulata da Silva (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Visual Communication Design is a study program that operates in the creative industry. Students are required to practice and dedicate their knowledge to the surrounding community, so that they can feel the benefits of the knowledge they gain. The lecturers involve students to join in applying knowledge to benefit society. The application of the knowledge gained during college includes basic drawing courses, nirmana dwimatra courses, and basic illustration courses. From the basics of this lecture, the lecturer is finally able to see how students are able to work. It is hoped that the resulting work will be able to have a good impact on the community around Sikka Regency and the wider community in East Nusa Tenggara. SDK Maumere 2 was founded in 1904 on July 28, but the government decree only took effect in 1981 on April 11. This Catholic elementary school area is located close to the St. Yosef Maumere Cathedral area and the school environment is located in the middle of Maumere city center. The buildings at SDK Maumere 2 have undergone several renovations and have begun to change from the original building to a newer building.  Utilization of the construction of each building in the SDK Maumere 2 area has maximized the availability of existing locations. The theme of the mural that will be created is the activities of elementary school students, the concept of the galaxy and the ocean. The part of the wall that will be depicted is the outer wall of the school. This mural activity was carried out based on a request from SDK Maumere 2 to create a more aesthetic school environment. It is hoped that this mural will be able to provide new enthusiasm in the school environment.